ARIMA and ARIMAX Modeling for Forecasting the Value of Non-Oil and Gas Exports - Alfisyahrina Hapsery; Artanti Indrasetianingsih; Saputri Dyah Pratiwi (Jurusan Matematika FMIPA Universitas Pattimura, 2026)
Non-oil and gas exports are the activity of selling commodities other than oil and gas abroad. Non-oil and gas exports are able to provide foreign exchange for the country, which can create jobs, increase competitiveness, and improve economic growth. The country that can create jobs, increase competitiveness and overall economic growth. So that this sector becomes the main focus of a country's economic policy. West Java is the province with the highest non-oil and gas exports value. In every year, the value of non-oil and gas exports has decreased. This is suspected to be due to the Eid al-Fitr holiday, where the decline is always there every year but in different months. So it is necessary to do statistical analysis to predict the value of non-oil and gas exports in West Java using the ARIMA and ARIMAX methods. West Java using ARIMA and ARIMAX methods with the effect of calendar variation as a dummy variable. The best model criteria are based on the smallest RMSE and MAPE values. The ARIMA model provides a better level of accuracy to predict the value of non-oil and gas exports with an RMSE value of 175176.59, MAE value of 130034.6, and MAPE of 4.09%.